2018
DOI: 10.56093/ijans.v88i9.83538
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis and haemato-biochemical changes in Anaplasma marginale infected dairy cattle

Abstract: The present study was a undertaken to diagnose Anaplasma marginale in naturally infected crossbred cows and to determine its effect on haemato-biochemical profile. Blood samples were collected from animals (200) for detection of the rickettsial organism by direct smear and direct blood PCR based techniques targeting the major surface protein 5 (MSP-5). Direct blood PCR revealed a 382-bp amplified fragment in positive control samples. When random blood samples were screened under light microscope and direct blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Genomic DNA extraction was performed on the blood samples using an inorganic method according to Saeed et al [24], and the DNA was stored at −20 • C until use. A set of oligonucleotide primers, Fwd 5 ACAGGCGAAGAAGCAGACAT3 and Rev 5 ATAAATGGGAACACGGTGGA 3 , was used to specifically amplify 382 base pairs of the msp5 gene of A. marginale in positive blood samples [25]. The reaction mixture was prepared in a final volume of 25 µL, containing 13 mM Tris-HCl (pH 8.3), 65 mM KCl, 2 mM MgCl2, 0.0013% gelatin, 300 µM of each dNTP, 1 U of AmpliTaq DNA polymerase, 0.5 µM of each primer and 5 µL (50 to 150 ng) of template DNA.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA extraction was performed on the blood samples using an inorganic method according to Saeed et al [24], and the DNA was stored at −20 • C until use. A set of oligonucleotide primers, Fwd 5 ACAGGCGAAGAAGCAGACAT3 and Rev 5 ATAAATGGGAACACGGTGGA 3 , was used to specifically amplify 382 base pairs of the msp5 gene of A. marginale in positive blood samples [25]. The reaction mixture was prepared in a final volume of 25 µL, containing 13 mM Tris-HCl (pH 8.3), 65 mM KCl, 2 mM MgCl2, 0.0013% gelatin, 300 µM of each dNTP, 1 U of AmpliTaq DNA polymerase, 0.5 µM of each primer and 5 µL (50 to 150 ng) of template DNA.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…The reaction mixture was prepared in a final volume of 25 µL, containing 13 mM Tris-HCl (pH 8.3), 65 mM KCl, 2 mM MgCl2, 0.0013% gelatin, 300 µM of each dNTP, 1 U of AmpliTaq DNA polymerase, 0.5 µM of each primer and 5 µL (50 to 150 ng) of template DNA. Reaction conditions included an initial denaturation step of 94 • C for 5 min, followed by 30 cycles of denaturation at 94 • C for 45 s, primer annealing at 53 • C for 50 s and extension at 72 • C for 50 s. A final extension at 72 • C for 7 min was performed [25]. Anaplasma marginale-positive and -negative samples were also added during each PCR reaction as positive and negative controls, respectively.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…Major surface proteins are highly conserved in Anaplasmataceae. Anaplasma marginale MSP5 can be used to identify and construct phylogenetic trees [16], as well as to identify carriers [11].…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma marginale MSP5 gene was amplified using extracted DNA and the indicated primer sets AMF: 5′-ACAGGCGAAGAAGCAGACAT-3′ and AMR: 5′-ATAAATGGGAACACGGTGGA-3′ [8,16].…”
Section: Molecular Detection Of Major Surface Protein 5 (Msp5) In a M...mentioning
confidence: 99%
“…Several studies in cattle have shown that natural or experimental infection with A. marginale is associated with significant changes in serum biochemical parameters comprising elevation in creatinine and bilirubin concentrations, some liver enzyme activities and some acute phase proteins and decline in serum total protein and albumin concentration (Allen et al, 1981;Coskun et al, 2012;Sharma et al, 2013;Jassem and agar, 2015;Ganguly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%